2020
DOI: 10.1111/myc.13068
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and characteristics of invasive fungal infections in critically ill burn patients: A multicenter retrospective study

Abstract: Background: Characteristics and outcome of invasive fungal infection (IFI) in critically ill burn patients have been poorly explored. Objectives:We report the factors associated with 90-day mortality in a multicentre retrospective European study.Patients/Methods: All burn patients with confirmed IFI admitted between 1 January 2010 to 31 December 2015 in 10 centres in France and Belgium were included. Results:Ninety-four patients were enrolled with 110 cases of IFIs: 79 (71.8%) were yeasts IFI and 31 (28.2%) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Invasive fungal infections are one of the most severe complications in burn patients and associated with poor outcomes ( Maurel et al., 2020 ). Burn wounds are the main sources of fungi in our center, similar to Pakistan ( Jabeen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive fungal infections are one of the most severe complications in burn patients and associated with poor outcomes ( Maurel et al., 2020 ). Burn wounds are the main sources of fungi in our center, similar to Pakistan ( Jabeen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that large burn area and depth, prolonged broad-spectrum antibiotic therapy, and increased postburn days were risk factors of fungal infections in burn patients ( Rafik et al., 2016 ; Jabeen et al., 2020 ). Bacterial coinfection and presence of allografts could further increase the mortality of patients with fungal infections ( Maurel et al., 2020 ). In this study, we also found 45.2% and 58.6% of patients with fungal infection complicated with bacterial infection in BCW and BICU, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3 By rectifying these discrepancies and instituting strategies to augment the accessibility of essential antifungal agents, healthcare institutions can enhance their capacity to handle IFI across a wider range of patients, in line with current guidelines. 15 , 30–34 This holds particular significance given the rising incidence of IFI among immunocompetent individuals, attributable to factors such as travel history to endemic regions, 35 , 36 burns 37 or traumatic injuries, 38 and more recently as a secondary infection to respiratory viral infections, including influenza- or severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2)-associated pulmonary aspergillosis. 9 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…In this situation, the positive rate of blood culture is considerably reduced. In addition, the incidence of fungal infections in elderly severe burn patients is very high [ 20 ], and blood cultures are insufficient for fungal detection due to the sensitivity deficiency and slow multiplication [ 21 , 22 ]. As an unbiased DNA/RNA detection method, mNGS is widely used in clinical practice but is rarely used in burn patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%